Factors affecting independent audit committee members' effectiveness - the case of listed firms on Bursa Malaysia - Mohd Saat, Nur Ashikin; Karbhari, Yusuf; Xiao, Jason Zezhong; Heravi, Saed (Billion Brains, 2012)
Studies on audit committee effectiveness have so far examined the relationship between significant presence of independent directors and the establishment of influential independent standpoint on the committee’s decision-making. However, independent composition does not necessarily guarantee audit committee members performance of financial oversight duties competently. This paper aims to investigate the characteristics of audit committee members in 221 listed firms in Bursa Malaysia. The results show that audit committee governing enhanced firm performance when there is high proportion of independent audit committee members with practicing accountant experience on the committee and firm explicitly disclosed the right of audit committee to report to the Stock Exchange of its breaching of Exchange and other regulatory rules. On the contrary, the relationship between composition of audit committee exclusively by independent director and the convening of independent committee members meeting with the external auditor without executive officers presence and firm performance is negative. The audit committee effectiveness is crucially dependent on audit committee members collective commitment to fulfil their oversight duties responsibly and management giving full co-operation and support to the access of required information for decision-making.